National Curriculum Development Models: Between Theory and Concept - Aiman, Ummu; Damapolii, Mujahid; Yanti K. Manoppo; Pantu, Ayuba (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Curriculum development aligns the current curriculum with expected educational goals through various positive influences from both external and internal sources, aiming to prepare students for their futures. Therefore, curriculum development should be adaptive, participatory, and applicable. This study aims to identify models of curriculum development. The research type employed is library research. Data sources are gathered from journals and books. The research data employ content analysis techniques. The findings of this study indicate that several models are utilized for curriculum development, including the Hilda Taba framework, the Tyler model, the Saylor, Alexander, and Lewis model, and the Olivia model. This suggests that curriculum development activities necessitate a model that serves as a theoretical foundation for implementing suitable activities.